The crown local assemblies (sejmiki koronne) and the peace with Turkey at the end of the 17th century: the treaty of Karlowitz and its political context in the Polish-Lithuanian Commonwealth - Zwierzykowski, Michał (Balcanica Posnaniensia. Acta et studia, 2003)
This article attempts to examine the attitude of Crown assemblies (sejmiki koronne) – a key institution of noble public opinion in the Polish-Lithuanian Commonwealth – towards the peace treaty of Karlowitz (1699). The aim is to analyse the approach of the nobility from the Crown lands of the Polish-Lithuanian Commonwealth to the political outcome of the war with Turkey and to the benefits associated with the established peace. The source material comes from a search of regional assembly instructions from 1690–1699, found in numerous archives and printed collections. Analysis of the materials showed that pacifist sentiments were strong among the nobility. The deputies' instructions included demands for a reduction in military expenditure, the termination of the alliance within the Holy League, and the expectation of a quick conclusion of a ‘perpetual peace’. Although the Treaty of Karlowitz merely restored the pre-war Polish-Ottoman borders, it was considered by most regional assemblies to be a great success that brought the desired stability. At the same time, however, there was a noticeable lack of reflection on the deeper causes of the weakening of the Republic's international position. The nobility's war weariness and shift towards defensive attitudes had an impact on the political culture of the late 17th century.